Square-Tiled Tori - Pardo-Jaqueih, A (American Institute of Mathematical Sciences, 2023)
We study square-tiled tori, that is, tori obtained from a finite collection of unit squares by parallel side identifications. Square-tiled tori can be parametrized in a natural way that allows to count the number of square-tiled tori tiled by a given number of square tiles. There is a natural SL(2, Z)action on square-tiled tori and we classify SL(2, Z)-orbits using two numerical invariants that can be easily computed. We deduce the exact size of every SL(2, Z)-orbit. In particular, this answers a question by M. Bolognesi on the number of cyclic covers of the torus, which corresponds to particular SL(2, Z)orbits of square-tiled tori. We also give the asymptotic behavior of the number of cyclic square-tiled tori. © 2023 American Institute of Mathematical Sciences. All rights reserved.
Keywords: Square-tiled surfaces; cyclic covers; Dedekind psi function